Selective Webliography for Health Sciences Authors - Mark A. Spasser (Issues in Science and Technology Librarianship)
This guide is intended to present a selected list of sites that cover the basic issues of writing for publication in professional medical venues and that provide useful information for health sciences authors who want either help with their writing or information resources that are 'ready to hand' (analogous to the physically located reference library). The subject headings are intended to offer a division of resources into heuristically useful categories. This selective webliography focuses on free quality online materials where possible. The primary purpose of this webliography is to assist clinicians and researchers -- health sciences professionals -- with the tasks of identifying, analyzing, and utilizing quality sites when bombarded with hundreds of sites listed by gateways and directories, and in results from search engine queries.